ANALISIS FUNGSI KEUNTUNGAN USAHATANI BAWANG MERAH (STUDI KASUS DI DESA TORONGREJO KECAMATAN JUNREJO KOTA BATU) - Elma Thiana; Bambang Siswadi; Farida Syakir (Program Studi Agribisnis, 2019)
ABSTRACT The purpose of this study was to determine the large costs, revenues, expenses, R/C ratios and the factors that affect the profitability of shallot farming. This research was conducted in Torongrejo Village, Junrejo Subdistrict, Batu City, because that place is one of the centers of shallot production in East Java. The research methods were descriptive and quantitative analysis. This study used simple random sampling method with 40 farmers. The data analysis that was used to analyze is descriptive methods and Cobb Douglass’s profit function. The results of the analysis stated that onion farming in Torongrejo Village, Junrejo District, Batu City was efficient and feasible to run and factors that affect the profitability of shallot farming were education, seed costs, tool depreciation costs and drug costs. While other factors such as land area, number of family members and labor costs were not affect the profits. Kata Kunci : Cobb Douglass's profit function, shallot farming.